Three-dimensional limit analysis of slopes reinforced with piles in soils exhibiting heterogeneity and anisotropy in cohesion. Issue 121 (June 2019) - Rao, Pingping; Zhao, Linxue; Chen, Qingsheng; Nimbalkar, Sanjay
Abstract: Reinforcement of slopes by placing piles is one of the most common and effective techniques. Most of existing studies are limited to homogeneous and isotropic slopes, while in practice, the soil in the slope often exhibits heterogeneous and anisotropic characteristics. To address these issues, an innovative approach is introduced in this Technical Note to evaluate the stability of heterogeneous and anisotropic slopes incorporating the effect of anti-slide piles. Employing a three-dimensional upper-bound limit analysis, safety factor adopting the strength reduction technique is utilized herewith. The effects of soil heterogeneity and anisotropy with reference to cohesion on the optimal pile location and the slope stability in both cohesive-frictional and purely cohesive soils are investigated. The results amply demonstrate that the proposed limit analysis is appropriate for the stability assessment of reinforced slopes in heterogeneous and anisotropic soils. The safety factor increases with increase in heterogeneous factor and decrease in anisotropic factor. The optimal pile location is irrespective of these two factors, which should be carefully considered in engineering design. Highlights: A 3D upper-bound limit approach is developed to evaluate the slope stability. Effect of anti-slide piles on slope stability is incorporated. Effects of soil heterogeneity and anisotropy are investigated. Slope stability in cohesive-frictional and purely cohesive soils are investigated. Safety factor adopting the strength reduction technique is utilized.